Korelasi Kemampuan Membaca Pemahaman dengan Kemampuan Menulis Resensi Siswa Kelas IX SMP Negeri 3 Linggo Sari Baganti - Fardengki, Fardengki; Emidar, Emidar; Noveria, Ena (Universitas Negeri Padang, 2012)
This research is proposed to described the third year studentsâ€™ reading comprehension at SMP Negeri 3 Linggo Sari Baganti, to describe the third year studentsâ€™ review ability at SMP Negeri 3 Linggo Sari Baganti, and to analyze the correlation between studentsâ€™ reading comprehension and review ability at SMP Negeri 3 Linggo Sari Baganti, this research used qualitative approach with coorelational method. Sample of this research was determined using proportional random sampling which taken 15% of the amount of the students each class. Based o research findings and data analysis, it can be inferred as follows: first, the ability of students reading comprehension at SMP Negeri 3 Linggo Sari Baganti can be classified as â€œgoodâ€ (70,10). Second, the ability of studentsâ€™ review can be classified as â€œgoodâ€ (73, 88). Third, there is a significance correlation between the third year studentsâ€™ reading comprehension and studentsâ€™ review ability at SMP Negeri 3 Linggo Sari Baganti which its reliability 95%.